2013
DOI: 10.1007/s10529-013-1296-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the anaerobic digestion of amine wastes

Abstract: Laboratory-scale anaerobic degradation of monoethanolamine waste (MEAw) with co-substrate organics was conducted at room temperature and organic loading rates from 0.19 to 5.03 kg COD/m3 day for 486 days in a hybrid digester. 90 % feed COD conversion to methane was obtained at the lower loads and only 45 % at the highest MEA waste/COD ratio (MEAwr) of 0.62 due to inhibition of methanogenesis. Inhibition at comparable loads decreased with time, implying that the culture adapted to the challenging feed. Methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Easily degradable organics: starch, glucose, peptone and yeast extract (Wang et al, 2013b) were used to codigest with MEAw in AD. The co-feed substrates were used to provid necessary nutrients, minerals and easily degradable organics for cultivating healthy biomass that can tolerate exposure to toxic and inhibitory chemicals from the MEAw.…”
Section: Co-feed Organics Specificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Easily degradable organics: starch, glucose, peptone and yeast extract (Wang et al, 2013b) were used to codigest with MEAw in AD. The co-feed substrates were used to provid necessary nutrients, minerals and easily degradable organics for cultivating healthy biomass that can tolerate exposure to toxic and inhibitory chemicals from the MEAw.…”
Section: Co-feed Organics Specificationmentioning
confidence: 99%
“…Measurements showed that MEAw COD varied in a range from 450 to 900 mg-COD/g-waste, where MEA COD was assumed to be constant at 44% of the MEAw COD and the rest (56%) was CO COD. According to measurements and calculations, the MEA and nitrogen fractions were around 18 to 30 wt% and 7 -14 wt%, respectively (Wang et al, 2013b). Alkalinity of the applied MEAw was measured to be 0.31 g/g MEAw (CaCO 3 equivalent) and was used to calculate the feed inorganic carbon concentrations in the model (Table. 2).…”
Section: Mea Waste Specificationmentioning
confidence: 99%
See 3 more Smart Citations